The Effects of Exergame Telerehabilitation in Persons With Subjective Cognitive Decline. - Salisbury, Dereck L; Pituch, Keenan A; Yu, Fang (Gerontologist, 2024)
Background and Objectives The primary aim of this Stage IB randomized controlled trial (RCT) was to test the preliminary effects of a dual-task exergaming telerehabilitation intervention on cognition and aerobic fitness, compared to aerobic exercise (AEx) only and attention control (stretching) in older adults with subjective cognitive decline. Research Design and Methods This RCT randomized 39 participants on a 2:1:1 allocation ratio to supervised exergame (n  = 20), AEx (n  = 11), and stretching (n  = 8) for 12 weeks. The dual-task exergaming was concurrent moderate-intensity cycling and BrainFitRx cognitive telerehabilitation. Cognition was assessed by NIH Toolbox Cognitive Battery and aerobic fitness by 6-minute walk test (6MWT) and shuttle walk test. Results The participants were 74.6 (7.4) years old and 69% were female. The effect of time was significant, F (1, 23.9) = 13.16, p  = .001, for the Fluid Composite score, and significant within-group changes were seen for the exergame group, t (14.08) = 2.53, p  = .024, d  = 0.33. Between-group changes did not reach significant levels for any cognitive test. Between-group changes for the 6MWT were not significant. Discussion and Implications The exergame participants further improved their fluid cognition, whereas the AEx and stretching groups did not, indicating a potential synergistic effect from AEx and cognitive training. The aerobic fitness changes were similar between the exergame and AEx-only groups, indicating that the feasibility of adding cognitive training to AEx concurrently without sacrificing gains in aerobic fitness from AEx. This study shows the flexibility of exergame delivery and its potentially therapeutic effects in persons at risk for Alzheimer's dementia. Clinical Trial Registration Number NCT04311736